HUBUNGAN EKUITAS MEREK (BRAND EQUITY) DENGAN LOYALITAS PELANGGAN PADA PT. ENSEVAL PUTERA MEGATRADING TBK CABANG BENGKULU - Sadad Radansyah; Nia Indriasari; Wagini Wagini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Sadad Radansyah, Nia Indriasari, The purpose of this study was to determine the correlation between brand equity with customer loyalty at Enseval Putera Megatrading Tbk Company BengkuluBranch. The analytical method used is Spearman’s rank correlation and hypothesis testing. Based on the Spearman correlation analysis of the correlation between brand equity with customer loyalty at Enseval Putera Megatrading Tbk Company Bengkulu Branchobtained the value of rho ( )the correlation between brand equity with customer loyalty at Enseval Putera Megatrading Tbk Company Bengkulu Branchis 0.841 at the interval of the correlation interpretation of 0.800-1,000, with very strong criteria, meaning the correlation between brand equity with customer loyalty at Enseval Putera Megatrading Tbk Company Bengkulu Branchis very strong. To test the hypothesis between brand equity and customer loyalty at Enseval Putera Megatrading Tbk Company Bengkulu Branchis obtained a calculated rho value greater than rho table (0.841> 0.364) so ​​that Ho is rejected and Ha is accepted, meaning that there is a significant correlation between brand equity and customer loyalty at Enseval Putera Megatrading Tbk Company Bengkulu Branch. Key Words: Liquidity,